Personalized approach to osteosubstitution with ceramic implants - Buyakov A. S. Ales Sergeevich; Kulkov S. N. Sergey Nikolaevich; Buyakova S. P. Svetlana Petrovna; Kulbakin D. E. (2017, 2017)
Заглавие с титульного экрана